27j-6=14j-7

Simple and best practice solution for 27j-6=14j-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27j-6=14j-7 equation:


Simplifying
27j + -6 = 14j + -7

Reorder the terms:
-6 + 27j = 14j + -7

Reorder the terms:
-6 + 27j = -7 + 14j

Solving
-6 + 27j = -7 + 14j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-14j' to each side of the equation.
-6 + 27j + -14j = -7 + 14j + -14j

Combine like terms: 27j + -14j = 13j
-6 + 13j = -7 + 14j + -14j

Combine like terms: 14j + -14j = 0
-6 + 13j = -7 + 0
-6 + 13j = -7

Add '6' to each side of the equation.
-6 + 6 + 13j = -7 + 6

Combine like terms: -6 + 6 = 0
0 + 13j = -7 + 6
13j = -7 + 6

Combine like terms: -7 + 6 = -1
13j = -1

Divide each side by '13'.
j = -0.07692307692

Simplifying
j = -0.07692307692

See similar equations:

| 112=7w-168 | | 30m=22+80m | | 2x+24=-30+5x | | 21x+7=10x-1 | | 5(g-6)=48 | | 1.5x=1.23 | | r-9-(-42)=96 | | 9+4+10=56 | | 8(3x+40)=10 | | x^2-320=x-10 | | 3overx= | | 15=k-32 | | 3x+2-2=8-2 | | 18p-15=0 | | T(-3)=21 | | 2X+1=-x+2 | | -x+(-x)+(-x)+(-z)= | | 1.6k=5.75 | | 2x+12=3x-9 | | (x^2)+30x-2000=0 | | n-11=66 | | 11y+5=3(-5+2y) | | -.9x^2+45x=0 | | 8x-12-6x-1=1 | | v-52=29 | | 2(6x-10)=31-3(5-3x) | | -24x+-6+7x+9x-27=4 | | p-6=43 | | h*7=15 | | -3x^2+36x-33=0 | | a^2-10+9a=0 | | 9(2x-3)=27 |

Equations solver categories